2014
DOI: 10.2174/1874210601408010168
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cavity Squamous Cell Carcinoma - Characteristics and Survival in Aboriginal and Non-Aboriginal Western Australians

Abstract: Background: Squamous cell carcinoma (SCC) is the most common type of malignancy affecting the oral cavity. While exposures to main risk factors for oral SCC such as smoking and alcohol use are higher amongst the Aboriginal people, little is known about oral cancer in this population. This study aimed to describe characteristics and survival of oral SCC in Aboriginal and non-Aboriginal Western Australians.Methods: All primary oral SCC cases reported to the Western Australian Cancer Registry (WACR) between 1990 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…In our study, inner regional suburbs Bundaberg Central and Rockhampton City along with Mount Isa which is classified as very remote suburb had the highest incidence risks [26]. Previously, three Australian studies conducted in regional Western Australia reported that an increasing number of oral cancer cases diagnosed in regional and remote areas are classified as in advanced stages of the disease [24,25,27]. Reasons for delay in diagnosis were reported to be regional isolation, lack of knowledge about the risk factors and symptoms, tobacco and alcohol abuse and HPV related oropharyngeal squamous cell carcinoma [27][28][29].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In our study, inner regional suburbs Bundaberg Central and Rockhampton City along with Mount Isa which is classified as very remote suburb had the highest incidence risks [26]. Previously, three Australian studies conducted in regional Western Australia reported that an increasing number of oral cancer cases diagnosed in regional and remote areas are classified as in advanced stages of the disease [24,25,27]. Reasons for delay in diagnosis were reported to be regional isolation, lack of knowledge about the risk factors and symptoms, tobacco and alcohol abuse and HPV related oropharyngeal squamous cell carcinoma [27][28][29].…”
Section: Discussionmentioning
confidence: 71%
“…Regionality plays a significant role in prevalence of chronic health issues in Australia [6,12,22,23]. This may be due higher risk behaviors, lack of awareness around healthy practices, level of education, and limited access to health care facilities [23][24][25]. In our study, inner regional suburbs Bundaberg Central and Rockhampton City along with Mount Isa which is classified as very remote suburb had the highest incidence risks [26].…”
Section: Discussionmentioning
confidence: 90%
“…Survival rates after 5 years for head and neck cancers in Aboriginal men in NSW were lower than for other men [ 5 ]. However, while squamous cell carcinoma was the most common malignancy affecting the oral cavity, there was no statistically significant difference in survival rates between Aboriginal and non-Aboriginal Australians living in Western Australia [ 6 ].…”
Section: Introductionmentioning
confidence: 99%